The Political Economy of Competitiveness: Corporate Performance and Public Policy. - Kitson, M; Michie, J (Routledge, 2000)
The authors use an interdisciplinary approach to the problem of economic growth, placing it in its historical and political context. Issues covered in the book include: trade theory and policy, industrial decline and policy, markets, competition and innovation, globalisation, unemployment and government policy.